Public Participation in the Budget Process: Theory and Methodology - D. T. Dzgoeva; I. S. Romanov (Управленческое консультирование)
This article analyzes various approaches to understanding public participation in the budget process of foreign and domestic researchers. In the context of the target approach, aspects related to understanding the goals of introducing public participation into the budget process of its possible participants are presented and systematized. In addition, an analysis was made of the motives of participants in public participation programs in the budget process. The relevance of the study is justified by the fact that the development of public participation in the budget process, in particular initiative budgeting, is one of the modern directions in the development of budget policy in the Russian Federation. The results of the study are, firstly, in the essential analysis of public participation in the budget process in political science discourse. Secondly, in the systematization of various approaches to determining the goals of introducing public participation in the budget process. Thirdly, in determining the motives of participants in public participation programs in the budget process. It was determined that a key element of public participation in the budget process is the continuity of the process of interaction between the public and public authorities. Understanding the goals and motives of public participation in the budget process differs among potential participants, however, the most interested in the implementation of public participation programs in the budget process are state authorities and citizens — non-profit and commercial organizations are less interested, but their participation makes it possible to provide additional resources for public participation programs in the budget process.